The principle of conventional control. Challenges in the framework of international law - Negro Alvarado, Dante Mauricio (2020)
This paper addresses the figure of conventional control and examines the possibilities of applying this concept within the framework established by the general international law and within the parameters determined by the control of constitutionality. We will address the figure of the diffuse conventional control as it has been used by the Inter-American Court of Human Rights, analizing it from the perspective of the theory of the sources of general international law; in the way in which different States of the region incorporate the international norm within their internal legal systems; and the hierarchy that they assign to said rules once they are incorporated.